Central venous catheter infection with Bacillus pumilus in an immunocompetent child: a case report - Riordan FAI; Dalzell AM; Bentur HN (BMC, 2007)
Abstract Background Bacillus organisms are common laboratory contaminants. The majority of Bacillus bacteraemias are transient and not clinically significant. Clinically significant infection due to Bacillus species is rare and mostly due to Bacillus cereus infections in immuno-compromised hosts. Case presentation We report a case of central venous catheter infection with Bacillus pumilus in an immunocompetent child with tufting enteropathy on long-term parenteral nutrition (PN). There were three episodes of central venous catheter infection with Bacillus pumilus in three months. Despite adequate and appropriate use of intravenous antibiotics, the infection failed to clear resulting in the need for removal of the catheter for complete cure. Conclusion Bacillus species can cause clinically significant central venous catheter infection, even in an immunocompetent host. Despite adequate antibiotic treatment, the central venous catheter may need removal for complete cure.